African Cassava Mosaic Disease: summary report - Alaux, Jean-Pierre (Technical Centre for Agricultural and Rural Cooperation, 1990)
This work was prompted by a desire to bring to the attention of cassava growers, particularly in Africa, currently available information about of main discases of this crop.